Toward a Gecko-Inspired, Climbing Soft Robot - Schiller, Lars; Seibel, Arthur; Schlattmann, Josef (Frontiers in Neurorobotics, 2019)
In this paper, we present a gecko-inspired soft robot that is able to climb inclined, flat surfaces. By changing the design of the previous version, the energy consumption of the robot could be reduced, and at the same time, its ability to climb and its speed of movement could be increased. As a result, the new prototype consumes only about a third of the energy of the previous version and manages to climb slopes of up to 84°. In the horizontal plane, its velocity could be increased from 2 to 6 cm/s. We also provide a detailed analysis of the robot’s straight gait.